Explaining the variability in the response of annual eusocial insects to mass‐flowering events. Issue 1 (26th October 2018) - Hovestadt, Thomas; Mitesser, Oliver; Poethke, Achim; Holzschuh, Andrea
Abstract: Empirical studies of annual eusocial insects in agricultural landscapes report contrasting findings with regard to colony responses to mass‐flowering of crops such as oilseed rape. In particular, total sexual production is often unaffected by such events, whereas worker number responds with a prominent increase. To resolve these conflicting observations, we model—using an established approach—the expected change in worker and sexual numbers in response to an increased worker productivity induced by mass‐flowering events at different times of the season. We find that the predicted response pattern is mainly shaped by the degree to which individual worker productivity is reduced by an increasing number of workers in the colony. Different environmental conditions and colony characteristics result in different levels of interference of workers, for example, during foraging or nest construction. Reduction in individual productivity is low, when worker interference is negligible ("weak limitation") and high when an increasing number of workers substantially decreases per‐capita efficiency ("strong limitation"). For weak limitation, any mass‐flowering event that ends before the production of sexuals starts has a strong multiplicative impact on both worker and sexual numbers. The magnitude of the effect is quite independent of the precise timing of such an event. After the onset of sexual production, mass‐flowering has a weaker effect, as the added resource supply is only linearly transferred into production of additional sexuals. For colonies under strong limitation, the predicted impact of mass‐flowering events is generally weaker, especially on the production of sexuals, and the timing of mass‐flowering events becomes more influential: Production of sexuals profits more from late than from early mass‐flowering events. Consequently, early mass‐flowering events are predicted to have a prominent effect on worker numbers but a negligible one on the output of sexuals. The model presented provides a mechanistic explanation of why increased worker abundances do not necessarily translate into increased production of sexuals. The model is also applicable to other eusocial insects such as paper wasps whenever brief pulses of massive resource availability shortly elevate resource intake rates above the "normal" levels. Abstract : The authors present a simple model to provide explanation for some (seemingly) contradictory observations in regard to the response of flower‐visiting (annual) social insects to "mass‐flowering events, " for example, flowering of oilseed rape, that increasingly occur in agricultural landscapes. The mass‐flowering phenomenon has raised suspicions that pollinator shortage might impair production of crops, in particular also in the context of ongoing climate change. They are able to elucidate the great importance of the timing of mass‐flowering events (with respect to the colonies' life cycle) and why mass‐flowering events may result in a noticeable increase in worker number but have little effect on the production of sexuals as has been observed in several empirical studies. The model is general enough to be applicable also to other social insects that are exposed to brief outbursts of greatly elevated resource availability.